Development Of Student Worksheets (LKPD) Based On The Problem Based Learning (PBL) Model On Statistical Material In Class X Of It High School - Muliana Muliana; Hayatun Nufus (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
Researchers are interested in conducting research with the title "Development of Student Worksheets (LKPD) Based on Problem Based Learning on Statistics Material for Class X SMA IT". This type of research is Research and Development (R&D) because this research will develop the development of Student Worksheets Based on Problem Based Learning on Statistics Material for Class X SMA IT. Research and development methods used to produce certain products, and test the effectiveness of these products. The location of this research was carried out at Lhokseumawe City IT High School in the odd semester of the 2023/2024 academic year. This research uses the ADDIE development model. (1). The validity of the results of the media expert validation questionnaire on the Problem Based Learning-based Student Worksheet in the Statistics material class X obtained an average percentage of 91.89% with very valid criteria and the results of the validation of the material experts on the Problem Based Learning LKPD the Statistics material of class X got an average percentage of 80.14% with valid criteria (2). The level of practicality from the results of small group educators' responses to the Problem Based Learning-based LKPD in the Statistics material of class X obtained an average percentage of 95% with very practical criteria (3). The level of effectiveness of the results of student completeness classically obtained an average percentage of 44% with fairly effective criteria and the response of large group students with an average percentage of 96% with very practical criteria. Therefore. Soo tis reserch valid, practices and effective with Problem Based Learning LKPD on Statistics class X material is effectively used.